IMPLEMENTASI PAKET VIII KEBIJAKAN EKONOMI PEMBANGUNAN DENGAN SATU PEMANFAATAN RUANG DAN PENGGUNAAN LAHAN DI INDONESIA (Jurnal Akuntansi, 2018)
Development is a very important activity in efforts to increase economic growth for Indonesia. Thus, the economic policies taken by the Government must be able to encourage, be sustainable and interrelated between one economic sector with the other sectors in order to achieve the expected goals. The regional autonomy policy is expected to be able to reduce this for the sake of shared prosperity, between the center and the respective regions. This study examines that the determination of the RTRW (Spatial and Regional Plan) is a matter that must be mutually agreed upon in order to formulate national economic development.